The Relative Importance of Institutional Trust in Countering Feelings of Unsafety in Disadvantaged Neighbourhoods - Persson, Monika (European Spatial Research and Policy, 2013)
The segregated nature of urban areas reflects an uneven exposure to risk and unsafety. This article analyzes the relevance of place to people’s feelings of unsafety by comparing questionnaire responses from people living in a segregated, disadvantaged neighbourhood to a random sample of people living in the same city. The results suggest that the central factors explaining the individual’s feelings of unsafety differ in this particular neighbourhood compared to the broader population. The article shows that place has a moderating effect on feelings of unsafety. Trust in public institutions is argued to be particularly important in segregated, disadvantaged neighbourhoods because of its potential to prevent feelings of unsafety.